Microwave Assisted Convenient One-Pot Synthesis of Coumarin Derivatives via Pechmann Condensation Catalyzed by FeF3 under Solvent-Free Conditions and Antimicrobial Activities of the Products - Vahid Vahabi; Farhad Hatamjafari (Molecules, 2014)
A rapid and efficient solvent-free one-pot synthesis of coumarin derivatives by Pechmann condensation reactions of phenols with ethyl acetoacetate using FeF3 as a catalyst under microwave irradiation is described. This one-pot synthesis on a solid inorganic support provides the products in good yields. The newly synthesized compounds were systematically characterized by IR, 1H-NMR, 13C-NMR, MS and elemental CHN analyses. The proposed solvent-free microwave irradiation method using the environmentally friendly catalyst FeF3 offers the unique advantages of high yields, shorter reaction times, easy and quick isolation of the products, excellent chemoselectivity, and a one-pot, green synthesis. The products were screened for antimicrobial activity, and the results showed that the compounds reacted against all the tested bacteria.